1998
DOI: 10.1086/515615
|View full text |Cite
|
Sign up to set email alerts
|

A Large Outbreak of Botulism: The Hazardous Baked Potato

Abstract: In April 1994, the largest outbreak of botulism in the United States since 1978 occurred in El Paso, Texas. Thirty persons were affected; 4 required mechanical ventilation. All ate food from a Greek restaurant. The attack rate among persons who ate a potato-based dip was 86% (19/22) compared with 6% (11/176) among persons who did not eat the dip (relative risk [RR] = 13.8; 95% confidence interval [CI], 7.6-25.1). The attack rate among persons who ate an eggplant-based dip was 67% (6/9) compared with 13% (24118… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(32 citation statements)
references
References 11 publications
2
30
0
Order By: Relevance
“…Angulo et al showed that 30 persons were intoxicated with C. botulinum type A after consuming potatoes [35], and Porshafi et al revealed type A as predominant [30]. Our study is consistent with these reports since it also determines type A as the dominant type in cheese samples and both the positive cases (100%) related to this type (Table 1).…”
Section: Discussionsupporting
confidence: 91%
“…Angulo et al showed that 30 persons were intoxicated with C. botulinum type A after consuming potatoes [35], and Porshafi et al revealed type A as predominant [30]. Our study is consistent with these reports since it also determines type A as the dominant type in cheese samples and both the positive cases (100%) related to this type (Table 1).…”
Section: Discussionsupporting
confidence: 91%
“…Due to technical difficulties (15) in quantitating the minor toxin in dual-toxinproducing strains, BoNT/A4 titers have been estimated only indirectly by neutralization of BoNT/B to estimate remaining toxicity of BoNT/A4 by mouse bioassay. The ratio of BoNT/B to BoNT/A4 toxicity has been roughly estimated to be between 10:1 and 100:1 (58,59). Thus, the recombinant BoNTs/A4 was constructed.…”
Section: Biosafetymentioning
confidence: 99%
“…Most outbreaks of foodborne botulism are caused by home-canned foods [4]. However, several large outbreaks in recent decades have been associated with commercial or restaurant foods [5][6][7]. Storage at inappropriate temperatures of a widely distributed commercial food product that contains C. botulinum spores could lead to large outbreaks of this potentially fatal disease.…”
mentioning
confidence: 99%